Is treatment with trimetazidine beneficial in patients with chronic heart failure? - Xiang Zhou; Jianchang Chen (PLoS ONE)
Background Whether additional benefit can be achieved with the use of trimetazidine (TMZ) in patients with chronic heart failure (CHF) remains controversial. We therefore performed a meta-analysis of randomized controlled trials (RCTs) to evaluate the effects of TMZ treatment in CHF patients. Methods We searched PubMed, EMBASE, and Cochrane databases through October 2013 and included 19 RCTs involving 994 CHF patients who underwent TMZ or placebo treatment. Risk ratio (RR) and weighted mean differences (WMD) were calculated using fixed or random effects models. Results TMZ therapy was associated with considerable improvement in left ventricular ejection fraction (WMD: 7.29%, 95% CI: 6.49 to 8.09, p<0.01) and New York Heart Association classification (WMD: -0.55, 95% CI: -0.81 to -0.28, p<0.01). Moreover, treatment with TMZ also resulted in significant decrease in left ventricular end-systolic volume (WMD: -17.09 ml, 95% CI: -20.15 to -14.04, p<0.01), left ventricular end-diastolic volume (WMD: -11.24 ml, 95% CI: -14.06 to -8.42, p<0.01), hospitalization for cardiac causes (RR: 0.43, 95% CI: 0.21 to 0.91, p = 0.03), B-type natriuretic peptide (BNP; WMD: -157.08 pg/ml, 95% CI: -176.55 to -137.62, p<0.01) and C-reactive protein (CRP; WMD: -1.86 mg/l, 95% CI: -2.81 to -0.90, p<0.01). However, there were no significant differences in exercise duration and all-cause mortality between patients treated with TMZ and placebo. Conclusions TMZ treatment in CHF patients may improve clinical symptoms and cardiac function, reduce hospitalization for cardiac causes, and decrease serum levels of BNP and CRP.